In water multicomponent synthesis of low-molecular-mass 4,7-dihydrotetrazolo[1,5-a]pyrimidines - Tkachenko, I. G.; Komykhov, S. A.; Musatov, V. I.; Shishkina, S. V.; Dyakonenko, V. V.; Shvets, V. N.; Diachkov, M. V.; Chebanov, V. A.; Desenko, S. M.; Швець, Володимир Миколайович (My University, 2019)
The three-component reaction of 5-aminotetrazole with aliphatic aldehydes (formaldehyde, acetaldehyde) and acetoacetic ester derivatives in water under microwave irradiation leads to the selective formation of 4,7-dihydrotetrazolo[1,5-a]pyrimidine derivatives. Under similar conditions using 4,4,4-trifluoroacetoacetic ester 5-hydroxy-4,5,6,7-tetrahydrotetrazolo[1,5-a]pyrimidines are obtained. The analogous reaction with acetylacetone requires scandium(III) triflate as catalyst. The antioxidant activity of selected compounds was assayed with 1,1-diphenyl-2-picrylhydrazyl.
Keywords: 5-aminotetrazole; antioxidant activity; 1,3-dicarbonyl compounds; multicomponent synthesis; tetrazolo[1,5-a]pyrimidines